1996
DOI: 10.1046/j.1365-2117.1996.00129.x
|View full text |Cite
|
Sign up to set email alerts
|

Tectonic control of fan size: the importance of spatially variable subsidence rates

Abstract: We study the geophysical controls on the size of alluvial fans. Simple relationships between catchment characteristics, sediment yield, subsidence patterns and fan size are developed. As predicting fan size is essentially a conservation of mass problem, our analysis is general, applying to all types of fan landform. The importance of spatially variable subsidence rates has gone largely unrecognized in previous studies of modern fans. Here we stress that the distribution of subsidence rates in the depositional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
80
1
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(85 citation statements)
references
References 12 publications
3
80
1
1
Order By: Relevance
“…The general relationship between drainage area and fan area was assessed from these data. Our findings concur with previous results identified by investigators of similar fans in arid settings (Bull, 1964;Hooke, 1968;Hooke and Rohrer, 1979;Leece, 1991;Whipple and Trayler, 1996) (Fig. 4).…”
Section: Classification and Definition Of Alluvial Fanssupporting
confidence: 96%
“…The general relationship between drainage area and fan area was assessed from these data. Our findings concur with previous results identified by investigators of similar fans in arid settings (Bull, 1964;Hooke, 1968;Hooke and Rohrer, 1979;Leece, 1991;Whipple and Trayler, 1996) (Fig. 4).…”
Section: Classification and Definition Of Alluvial Fanssupporting
confidence: 96%
“…In practice this choice has little impact on the overall results, because the hillslope/ colluvial reach represents a very short section of the profile as a whole. We fixed the simulated outlet ele- vation to match the observed outlet elevation, reasoning that the glacial system has had very little opportunity to modify this elevation by either erosion (very short ice residence time in this region even for the fully glaciated cases) or by deposition (most of the sediment continues to the alluvial/debris flow fans below (Whipple and Trayler, 1996), and beyond). This is consistent with (i) the observation (Fig.…”
Section: -D Simulationsmentioning
confidence: 98%
“…Previous studies of alluvial fans have demonstrated that these landforms afford considerable potential to contribute to this debate, not least because their limited extent (length) may promote relatively rapid and complex response to both internal and external perturbations (Hooke and Dorn, 1992;Harvey, 2002a;Viseras et al, 2003). Fieldbased interpretation of fan morphology and stratigraphy has often emphasized the role of external environmental forcing (Ritter et al, 1995;Whipple and Trayler, 1996;Harvey, 2002b;Hartley et al, 2005;Harvey, 2005). For example, Figure 1 shows a heavily entrenched tributary fan in the Avoca Valley, South Island, New Zealand, which could be interpreted to reflect a para-glacial decline in sediment supply (cf.…”
mentioning
confidence: 99%